The Environmentality of Immersive Projection: The Nature of Scale (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
How does an artwork express an “environmentality?” Can we redefine immersion, in critical terms, as a form of environmental projection? In taking up such questions from my latest book, Atmospheres of Projection: Environmentality in Art and Screen Media, my text addresses the relation between projection and environmentality in the visual arts in order to question immersivity. Confronted with the phenomenon of environmentalization, we need to re-imagine the ecology of representation. Positing ecology as an environmental relation, I will consider its artistic imagination both historically and theoretically. I propose that we revisit the environmentality of media archaeology to understand how this impulse is furthered in current moving-image projections in the art gallery that call themselves immersive. I will especially address environmentality as it relates to movement and scale, questioning the relation between immersion and magnification. I will advance my argument by presenting the large-scale moving-image installations of the Danish-born, New York artist Jesper Just. Does magnification always, only imply spectatorial immersion? Other forms of experience arise when confronting an ecology of scale in art. What else happens when we scale? Can immersion be understood, more critically, as a form of environmental absorption? In recasting immersion in environmental terms, I propose that we consider absorption as empathic projection with space. In shifting from the human subject’s own immersive identification to this critically aware, enveloping field of empathic projection with the non-human, we can discard the prevalent human-centric position that pervades most immersive discourses. A different ecology of immersivity rises to the surface by relating the empathic “projective imagination” to “atmospheric thinking.”
Keywords: Ecology of Immersivity; Atmospheric thinking; Empathy and immersion; Scale and magnification; Jesper Just